10 Global economic evaluation of population-based BRCA1/BRCA2 mutation testing. (18th September 2019) - Manchanda, R; Sun, L; Patel, S; Wilschut, J; Lopes Carolina de Freitas, A; Brentnall, A; Duffy, S; Cui, B; Soarez Coelho de, P; Husain, Z; Vanni, T; Hopper, J; et al.
Abstract : Objectives: To evaluate cost-effectiveness and population-impact of unselected population-based BRCA -testing compared to clinical-criteria/family-history(FH) based BRCA -testing across Lower-middle-income/LMIC (India), Upper-middle-income/UMIC (Brazil/China) and High-income-countries/HIC (US/UK/Netherlands) health-systems. Methods: Markov-modelling compared lifetime costs-&-effects of BRCA1/BRCA2 -testing all general-population women ≥30years compared with clinical-criteria/FH-based testing. Analyses undertaken for UK/USA/Netherlands/China/Brazil/India using both health-system/payer and societal perspectives. All women ≥30years in the Population-Testing arm and only those fulfilling clinical/FH-criteria in the Clinical-Criteria/FH-based testing arm undergo BRCA -mutation testing. We collected primary-data on direct medical costs from China, Brazil, India. Costing-data were obtained from published NHS-reference-costs for the UK/Netherlands and published literature for USA. Future costs/health-effects discount-rate=3.5%. Parameter-uncertainty was explored using one-way and probabilistic-sensitivity-analyses. Specific health-economic cost-effectiveness threshold guidelines were used where available for UK=£20, 000-£30, 000; USA=$50, 000-$100, 000; Netherlands=€20, 000-€50, 000. Main-outcome=ICER/QALY. For comparison local currency values are converted to $s using purchasing-power-parity factor. Results: From 'societal-perspective', population-based BRCA -testing is 'cost-saving' in HIC: UK-ICER=$-3, 508/QALY; USA-ICER=$-1, 327/QALY; Netherlands-ICER=$-8, 663/QALY. It is potentially Cost-effective in UMIC depending on willingness-to-pay thresholds chosen and genetic-testing costs. UMIC-ICERs are just above 1*GDP-threshold: China-ICER=$20, 988/QALY; Brazil-ICER=$15, 587/QALY. It becomes under 3*GDP threshold in India if BRCA -testing cost is $148/test (ICER=$19, 676/QALY). From 'payer-perspective', population-based BRCA -testing is cost-effective in HIC: UK-ICER=$24, 101/QALY; USA-ICER=$19, 804/QALY; Netherlands-ICER=$28, 668/QALY. Results are sensitive to genetic-testing costs. Population-based BRCA -testing can prevent an additional 2319-to-2666 breast-cancers and 327-to-449 ovarian-cancers/million-women translating to tens-of-thousands more breast/ovarian-cancers prevented across the population. Conclusions: Population-based BRCA -testing is cost-effective in HIC and potentially in UMIC depending on the local willingness-to-pay thresholds. Genetic-testing costs need to fall further for LMIC cost-effectiveness. Population-testing can prevent tens-of-thousands more breast/ovarian-cancers than the current clinical strategy.